2009
DOI: 10.1007/s00134-009-1408-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide monitoring during long-term noninvasive respiratory support in children

Abstract: Nocturnal hypercapnia may occur in children receiving nocturnal noninvasive respiratory support at home. Nocturnal pulse oximetry and daytime arterial blood gases are not sufficiently accurate to diagnose nocturnal hypercapnia, underlying the importance of a systematic carbon dioxide monitoring in children receiving noninvasive respiratory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 15 publications
3
78
1
5
Order By: Relevance
“…10 Three different criteria were used to define abnormal S pO 2 , in separate analyses: a value Յ 88% for at least 5 consecutive minutes (criterion 1), 1 mean nocturnal S pO 2 Ͻ 90% or S pO 2 Ͻ 90% during Ն 10% of the total recording time (criterion 2), 6,11 and mean nocturnal S pO 2 Ͻ 92% or S pO 2 Ͻ 92% during Ն 10% of the total recording time (criterion 3). 5 …”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…10 Three different criteria were used to define abnormal S pO 2 , in separate analyses: a value Յ 88% for at least 5 consecutive minutes (criterion 1), 1 mean nocturnal S pO 2 Ͻ 90% or S pO 2 Ͻ 90% during Ն 10% of the total recording time (criterion 2), 6,11 and mean nocturnal S pO 2 Ͻ 92% or S pO 2 Ͻ 92% during Ն 10% of the total recording time (criterion 3). 5 …”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…1 Studies have shown that simultaneous recording of transcutaneous carbon dioxide partial pressure (P tcCO 2 ) and pulse oximetry (S pO 2 ) is the best method for assessing the efficiency of nocturnal home MV in improving blood gas values [1][2][3][4][5] and detecting prolonged AH and short periods of sleep-related breathing disorders (leaks, asynchrony, and glottis closure). However, to save time and diminish costs, screening with nocturnal pulse oximetry alone, which is easier than recording P tcCO 2 , especially at home, has been suggested as a means of identifying those patients who require further nocturnal investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies suggest that PtcCO 2 monitoring during sleep is not reliable because of the occurrence of sharp changes caused by the patients' movements during sleep [13,14], other studies comparing PtcCO 2 monitoring to ABG measurements in children during polysomnographies, in intensive care patients, in patients with non-invasive mechanical ventilation support, and in perioperative patients have proven this method's reliability [15][16][17][18][19][20][21]. The AASM recommends PtcCO 2 monitoring for patients suspected to have obesity hypoventilation syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Routine transcutaneous PCO 2 (PtcCO 2 ) monitoring has minimal clinical use in adult polysomnographies; its slow response time makes it unsuitable for monitoring blood gas pressures during sleep, in which rapid and short-lasting changes can occur. PtcCO 2 monitoring may be of some use in adults with waking hypercapnia or suspected sleep-related alveolar hypoventilation [13,14]; however, many studies have shown that continuous PtcCO 2 monitoring is useful in monitoring and diagnosing sleep-related breathing disorders, especially in children, intensive care patients, patients with non-invasive mechanical ventilation support, and perioperative patients [15][16][17][18][19][20][21]. The American Academy of Sleep Medicine (AASM) manual for scoring sleep mentioned both end-tidal PCO 2 and PtcCO 2 measurements as being optional for hypoventilation scoring [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nocturnal hypercapnia may be present in CLD without nocturnal hypoxemia or daytime gas-exchange abnormalities. [3][4][5][6] Increased upper airway resistance, including nasal obstruction, is a risk factor for obstructive sleep apnoea (OSA). Cystic fibrosis (CF) and primary ciliary dyskinesia (PCD) are associated with a high incidence of chronic sino-nasal disease, including nasal polyps.…”
mentioning
confidence: 99%